Blue rubber bleb nevus: a rare cause of GI bleeding—review of management - Ur Rashid, Mamoon (BMJ Case Rep, 2019)
Blue rubber bleb nevus syndrome (BRBNS) is a rare congenital vascular anomaly syndrome characterised by multifocal venous vascular malformations. It involves skin, central nervous systems, liver, muscles and gastrointestinal (GI) tract resulting in intestinal haemorrhage and anaemia. Patients with BRBNS experience severe chronic anaemia without any diagnosis requiring multiple transfusions and hospitalisations. BRBNS has a propensity for severe life-threatening bleeding. Skin and GI tract are the most commonly affected organs.